Penyuluhan cara belajar siswa yang efektif dan pembagian alat tulis kepada siswa Sekolah Dasar Negeri 54 di Kampung Aipiri, Distrik Manokwari Timur: Counseling on effective student learning method and distribution of stationary to students of state primary school 54 in Aipiri Vilage, East Manokwari District - Santoso, Budi; Nunaki, Jan H.; Rumatumia, Zainudin; Ick, Loisa A.; Inggesi, Barsalina J. (IGKOJEI: Jurnal Pengabdian Masyarakat, 2025)
ABSTRACT  Learning is a form of conscious effort made by individuals to obtain behavioral changes through training and experience involving cognitive, affective and psychomotor aspects to achieve certain goals. In the process of learning activities, students have different learning tendencies such as visual and auditory learning styles. Therefore, different strategies are needed to obtain optimal results.. The purpose of this activity was to provide students with an understanding of how to learn effectively and at the same time provide stationery assistance to support the learning process for students at Primary School 54, in Aipiri Village. This counseling was carried out at Primary School 54 Aipiri, Aipiri Village, East Manokwari District. This activity was attended by 23 people consisting of 21 students and 2 teachers. This activity was carried out through 3 stages, namely the preparation stage, counseling and distribution of stationery. Counseling was carried out using lecture and discussion methods using visual media tools, power point slides and videos. The results of the activity showed that the counseling participants were very enthusiastic about participating in this activity, which was indicated by the activeness of the students in asking questions and answering questions from the Community Service Team. Some effective ways for students to learn include (1) how to study in groups; (2) how to read books; (3) how to take notes; (4) how to follow lessons; (5) how to repeat lessons; (6) how to concentrate and (7) how to memorize lessons. At the end of the activity, stationery distribution was handed over to the school principal and stationery was distributed to students. It was concluded that the application of effective and efficient learning methods can significantly improve student learning outcomes.  Keywords: Aipiri; Learning Method; Effective; Counseling; Student.   ABSTRAK  Belajar merupakan suatu bentuk usaha sadar yang dilakukan oleh individu untuk memperoleh perubahan tingkah laku baik melalui latihan dan pengalaman yang menyangkut aspek kognitif, afektif dan psikomotorik untuk memperoleh tujuan tertentu. Dalam proses kegiatan belajar, siswa memiliki kecenderungan cara belajar yang berbeda-beda seperti gaya belajar visual, auditori. Oleh karena itu dibutuhkan strategi yang berbeda pula untuk bisa mendapatkan hasil yang optimal.  Tujuan kegiatan ini untuk memberikan pemahaman kepada pada siswa tentang cara belajar yang efektif dan sekaligus memberikan bantuan alat tulis untuk mendukung proses pembelajaran bagi siswa/siswi di SD Negeri 54, di Kampung Aipiri.  Penyuluhan ini dilaksanakan di Sekolah Dasar Negeri 54 Aipiri Kampung Aipiri, Distrik Manokwari Timur.  Kegiatan ini diikuti 23 orang terdiri atas 21 orang siswa dan 2 orang guru.  Kegiatan ini dilakukan melalui 3 tahap yaitu tahap persiapan,  penyuluhan dan pembagian alat tulis.  Penyuluhan dilakukan menggunakan metode ceramah dan diskusi dengan menggunakan alat bantu media visual slide power point dan video.  Hasil kegiatan menunjukkan peserta penyuluhan sangat antusias mengikuti kegiatan ini yang diindikasikan dengan keaktifan siswa/siswi untuk mengajukan pertanyaan dan menjawab pertanyaan dari Tim Pengabdi.  Beberapa cara belajar siswa yang efektif meliputi (1) cara belajar kelompok; (2) cara membaca buku; (3) cara membuat catatan; (4) cara mengikuti pelajaran; (5) cara mengulang pelajaran; (6) cara melakukan konsentrasi dan (7) cara menghafal pelajaran.  Pada akhir kegiatan dilakukan penyerahan bantuan alat tulis kepada kepala sekolah dan pembagian alat tulis kepada siswa.  Disimpulkan bahwa penerapan metode belajar yang efektif dan efisien dapat meningkatkan hasil belajar siswa secara signifikan.    Kata kunci: Aipiri; Cara Belajar; Efektif; Penyuluhan; Siswa.